Economic Evaluation of a Point-of-Care Test for Bacterial Vaginosis Among Women With Vaginal Symptoms. Issue 5 (11th May 2023) - Jiao, Boshen; Fredricks, David N.; Srinivasan, Sujatha; Hansen, Ryan
Abstract : This modeling study demonstrates that using a point-of-care test to diagnose bacterial vaginosis is likely to be cost-effective, especially with a high sensitivity or a substantial positive effect on productivity. Abstract : Background: There is an unmet need for a clinical diagnostic technology to detect bacterial vaginosis (BV) rapidly and accurately. Novel point-of-care (POC) tests have the potential to fulfill this gap. Our objective was to determine the cost-effectiveness of a hypothetical clinician-administered POC test for diagnosing BV in the United States. Methods: We developed a state-transition microsimulation model to evaluate the cost-effectiveness of using the POC test versus usual care among women of reproductive age with vaginal symptoms. We adopted a healthcare sector perspective that included relevant healthcare costs and a societal perspective that further incorporated productivity costs. Model parameters were empirically estimated based on commercial insurance claims data or derived from published literature. The primary model outcome was incremental cost-effectiveness ratio. We started with analyzing a hypothetical POC test with a sensitivity and specificity of 0.9 and a cost of $40, followed by extensive sensitivity analyses. Results: Using the hypothetical POC test to diagnose BV increased costs by $16 and quality-adjusted life-years by 0.0005 per person compared with the usual care, leading to an incremental cost-effectiveness ratio of $31, 108 per quality-adjusted life-year gained. When also capturing the productivity costs, the POC test resulted in an average cost savings of $57. The sensitivity analyses showed that the POC test's sensitivity was more influential on its cost-effectiveness than specificity. Conclusions: Using the POC test to diagnose BV is likely to be cost-effective relative to usual care, especially with a high sensitivity or a substantial positive effect on productivity.